Estimation of delay during waiting at CIQ complex and its implication - Nor Syazana Nor Sukri, 1989-, author; Chitrakala Muthuveerappan, supervisor; Fakulti Geoinformasi dan Harta Tanah (2012)
Project Paper (Sarjana Muda Sains (Pengurusan Harta Tanah)) - Universiti Teknologi Malaysia, 2012